Ottolander Role in Tamansari Banyuwangi 1909-1933 - Laili, Ulfi Nurul; Soetopo, Dhalia; Nurullita, hervina (Siginjai: Jurnal Sejarah, 2025)
This research examines the role of Ottolander, a Dutch figure who played an important role in the development of coffee plantations and cultural preservation in Tamansari, Banyuwangi in 1909-1933. Using the historical method which includes the stages of heuristics, criticism, interpretation and historiography. This study aims to reconstruct Ottolander's contribution in the Dutch East Indies colonial context. Ottolander was known as a smart and insightful plantation entrepreneur, and was active in agricultural organizations such as the Naerlandsh Indische Landbouw syndicaat. He also introduced gandrung Banyuwangi to the national level through the Java-instituut congress in 1921. During Ottolander's presence in Tamansari not only increased coffee production, but also had a positive impact on the local residents. Ottolander also provided a little knowledge to local residents through agricultural training.